Cultural Perceptions of Santri on Arabic Language Learning - Yoyo Yoyo; Mohamad Hussin; Arif Rahman; Abdul Razif Zaini; Sutipyo R (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2023)
The study delves into the perceptions of santri concerning Arabic cultural elements in the teaching of the Arabic language within Salafi Pesantren. Employing a qualitative approach, the research investigates how santri perceive the significance of Arabic cultural values in the learning process and the broader implications for multicultural understanding. Data were gathered through interviews and questionnaires distributed to 42 respondents across 16 Salafi pesantren institutions in various regions of Indonesia, including Java, Sumatra, and Sulawesi. The findings reveal that santri generally recognize the importance of incorporating Arabic cultural elements into the language-learning process, as it aids in comprehending both the Arabic language and its cultural nuances. Some aspects of Arabic culture are perceived by santri as integral to Islamic teachings, influencing distinctive practices in their clothing and physical appearance. Despite these unique practices, the santri, living in a multicultural society, choose to integrate their daily lives with other communities, fostering harmony and embracing the multicultural diversity present in Indonesia. This study contributes valuable insights into the intersection of language learning, cultural values, and multicultural coexistence in the context of Salafi Pesantren education.